2021
DOI: 10.1038/s41598-021-91256-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tiger milk mushroom (Lignosus rhinocerus) supplementation on respiratory health, immunity and antioxidant status: an open-label prospective study

Abstract: Tiger milk mushroom (TMM; Lignosus rhinocerus) have been used for a long time by indigenous communities in South East Asia regions as traditional medicine for different ailments, including respiratory disorders. The beneficial effects of TMM have been proven through in vivo and in vitro models, but these effects have yet to be validated in a clinical study. In this study, the beneficial effects of TMM supplementation were investigated in 50 voluntary participants. Participants were required to take 300 mg of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 77 publications
0
12
0
1
Order By: Relevance
“…Nowadays, β-glucans have gained appeal for several emerging applications, including biopolymers 40 and biomedicines 41 . Notable potential therapeutic properties recently uncovered of mushroom-derived β-glucans include: (a) new or complementary immunotherapies against Coronavirus disease (SARS-CoV-2) 18 ; (b) new therapeutic agent for mitigating diseases associated with gastrointestinal mucosal damage, such as peptic ulcers and inflammatory bowel disease 42 ; (c) anticancer drugs for lung and breast cancer 43 ; and (d) asthmatic treatment 28 , 44 . However, there is a substantial gap in knowledge surrounding the toxicity (if any) of these mushroom-derived bioactive compounds, particularly on MB-EPS extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, β-glucans have gained appeal for several emerging applications, including biopolymers 40 and biomedicines 41 . Notable potential therapeutic properties recently uncovered of mushroom-derived β-glucans include: (a) new or complementary immunotherapies against Coronavirus disease (SARS-CoV-2) 18 ; (b) new therapeutic agent for mitigating diseases associated with gastrointestinal mucosal damage, such as peptic ulcers and inflammatory bowel disease 42 ; (c) anticancer drugs for lung and breast cancer 43 ; and (d) asthmatic treatment 28 , 44 . However, there is a substantial gap in knowledge surrounding the toxicity (if any) of these mushroom-derived bioactive compounds, particularly on MB-EPS extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Bioactive compounds, such as -glucans, were found in these L. rhinocerus MB-EPS extracts; use of glucans have gained appeal in recent years for a number of emerging applications including biopolymers 30 and biomedicines 31 . It is notable that mushroom-derived -glucans have many new therapeutic properties, including (a) potential new or complementary immunotherapies against Coronavirus disease (SARS-CoV-2) 14 , (b) potential new therapeutic agent for mitigating diseases associated with gastrointestinal mucosal damage, such as peptic ulcers and inflammatory bowel disease 32 , (c) potential as anticancer drugs for lung and breast cancer 33 , and (d) potentially asthmatic treatment 23,34 . However, there is a marked gap in knowledge surrounding the toxicity (if any), of these mushroom-derived bioactive compounds; particularly use of Zebrafish trials that would aid product development and implementation.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to dried polysaccharides, powdered MB is more applicable for pharmaceutical industry. The latter is notable as 300 mg of dry tuber biomass from the Malaysian L. rhinocerus has been reported to potentially improve respiratory health in both in vivo and in vitro models 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The properties and biological activities associated with mushrooms here summarised could have a potential interest in several industries belonging to pharmaceutic or/and nutraceutical fields. In order to advance in the application of mushroom bioactives in the formulation of novel foods, further work is required in relation to the adoption of a holistic approach for mushroom utilisation in functional food (Mingyi et al ., 2019); to the definition of the particular bioactive compounds in mushrooms, enabling that the findings be adopted into clinical practice and replication of studies in different population groups (Blumfield et al ., 2020); or in vivo studies to determine the appropriate doses, side effects and action spectrum of different bioactive compounds and fractions (Tan et al ., 2021).…”
Section: Conclusion and Future Trendsmentioning
confidence: 99%
“…Mushrooms have been reported to possess hypocholesterolaemia, antimicrobial, antioxidant, hepatoprotective, cardiometabolic regulator, immunomodulatory, antitumoral, neuroprotective, prebiotic and antiobesity effects (Gaitán‐Hernández et al ., 2019; Kumar, 2020; Tan et al ., 2021). In addition to some recent reviews focused on the biological properties of particular species (Gaitán‐Hernández et al ., 2019; Blumfield et al ., 2020; Kumar, 2020; Lin et al ., 2020), abundant studies on mushroom polysaccharides can be found (Mingyi et al ., 2019; Yin et al ., 2020; Wang et al ., 2022), and recent discoveries, new extraction techniques and bioactivities have been updated (Rodrigues Barbosa et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%